2005
DOI: 10.1007/s00422-005-0029-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling electromagnetic fields detectability in a HH-like neuronal system: stochastic resonance and window behavior

Abstract: Noise has already been shown to play a constructive role in neuronal processing and reliability, according to stochastic resonance (SR). Here another issue is addressed, concerning noise role in the detectability of an exogenous signal, here representing an electromagnetic (EM) field. A Hodgkin-Huxley like neuronal model describing a myelinated nerve fiber is proposed and validated, excited with a suprathreshold stimulation. EM field is introduced as an additive voltage input and its detectability in neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 51 publications
0
25
0
1
Order By: Relevance
“…According to this idea, Apollonio et al [22,23] proposed a complete quantitative evaluation of the effects of electromagnetic fields on neurons. However, a recent study [24] concluded that performing a comprehensive study of the non-thermal effects of electromagnetic radiation is only possible through a multi-scale methodology.…”
Section: Introductionmentioning
confidence: 99%
“…According to this idea, Apollonio et al [22,23] proposed a complete quantitative evaluation of the effects of electromagnetic fields on neurons. However, a recent study [24] concluded that performing a comprehensive study of the non-thermal effects of electromagnetic radiation is only possible through a multi-scale methodology.…”
Section: Introductionmentioning
confidence: 99%
“…The exogenous EM field was introduced in the network model as an additive component over the membrane potential [12], [13]. In such an hypothesis the EM field can be represented as a voltage generator, in series with membrane capacitor and ionic conductances, as shown in Fig.1 [6].…”
Section: Enhancement Of Em Signal Detectability In a Realisticmentioning
confidence: 99%
“…The detectability of input EM fields by means of a suitable amount of endogenous noise has already been shown by the authors [6], on the basis of a stochastic resonant behavior in a realistic single neuron model.…”
Section: Introductionmentioning
confidence: 96%
“…The magnetic field changes were measured by a noninvasive medical device, which has been supplied on the market for over 10 years. This magnetic test, using a polarized light can detect a defect at the cellular level (Gianni & Liberti, 2006). Humans have an electromagnetic energy field, the human body is an aerial that can transmit and receive energy (William, 2002).…”
Section: Pulsed Electromagnetic Field (Pemf) Testmentioning
confidence: 99%